Quantum interrogation of imperfect absorbers using post-selection - Muhammad Abdullah Ijaz; Syed Bilal Hyder Shah; Muhammad Sabieh Anwar (JPhys Photonics)
We propose a scheme for quantum interrogation measurements using constructive interference and post-selection to achieve single-pass high-efficiency detection for imperfect absorbers. We illustrate that our method works for heralded single-photon and weak attenuated sources. We also study the influence of noise in our experimental implementation and show that post-selection imparts additional robustness to the scheme against noise. We further demonstrate that fringe visibility from post-selection interferometry can be used to quantify the transmittance of the imperfect absorber. An interesting link between the interrogation and weak values of nonunitary operators is also highlighted.